Reflective and beam-through types of fiber optic sensor for displacement measurement / by Walaa Fawzi al-Masri - Al–Masri, Walaa Fawzi (2010)
This dissertation proposes and demonstrates fiber-optic displacement sensor (FODS) theoretically and experimentally using the intensity modulation technique to measure a displacement from a probe and target. The sensor uses a multimode plastic bundled fiber as a probe and He-Ne laser as a source. The performance of the sensor is compared for different type of probe and target. For a pair type bundled fiber, both the experimental and theoretical results exhibit the same type of characteristic features. The front slope sensitivities are obtained at 1.71 and 1.0 mW/μm for the theoretical and experimental approaches respectively, while the back slope sensitivities are 0.38 and 0.22 mW/μm for the theoretical and experimental approaches respectively, which is smaller than the front slope. By comparing a different type of probe, the result shows that the probe with the largest receiving core diameter demonstrates the highest linearity range, and increasing the number of receiving cores increases the sensitivity of the sensor. With a stainless steel target and the concentric bundled fiber with 16 receiving fibers as a probe, the sensitivity of the sensor is found to be 0.0220 mV/μm over 150 to 550 μm range and -0.0061 mV/μm over 1100 to 2000 μm range. For the beam through type of FODS, only one linear slope is observed. The effect of lateral and axial displacements is investigated. The highest sensitivity is obtained at 0.0008 mV/μm for the lateral displacement. The widest linear range is obtained at 3195mm for the axial displacement.